Renewable energy in copper production: A review on systems design and methodological approaches. (10th February 2020) - Moreno-Leiva, Simón; Haas, Jannik; Junne, Tobias; Valencia, Felipe; Godin, Hélène; Kracht, Willy; Nowak, Wolfgang; Eltrop, Ludger
Abstract: Renewable energy systems are now accepted to be mandatory for climate change mitigation. These systems require a higher material supply than conventional ones. Particularly, they require more copper. The production of this metal, however, is intensive in energy consumption and emissions. Therefore, renewable energy systems must be used to improve the environmental performance of copper production. We cover the current state of research and develop recommendations for the design of renewable energy systems for copper production. To complement our analysis, we also consider studies from other industries and regional energy systems. We provide six recommendations for future modeling: (a) current energy demand models for copper production are overly simplistic and need to be enhanced for planning with high levels of renewable technologies; (b) multi-vector systems (electricity, heat, and fuels) need to be explicitly modeled to capture the readily available flexibility of the system; (c) copper production is done in arid regions, where water supply is energy-intensive, then, water management should be integrated in the overall design of the energy system; (d) there is operational flexibility in existing copper plants, which needs to be better understood and assessed; (e) the design of future copper mines should adapt to the dynamics of available renewable energy sources; and (f) life cycle impacts of the components of the system need to be explicitly minimized in the optimization models. Researchers and decision-makers from the copper and energy sector will benefit from this comprehensive review and these recommendations. We hope it will accelerate the deployment of renewables, particularly in the copper industry. Highlights: Copper is required to build energy systems of the future. Smart integration of renewables can lower the cost of cleaner copper production. We provide six recommendations to model these systems. Further efforts are required in the modeling of energy demand and flexibility. Following these recommendations will enable cleaner and cheaper designs.